2018
DOI: 10.1016/s1473-3099(18)30423-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose versus 7-day-dose metronidazole for the treatment of trichomoniasis in women: an open-label, randomised controlled trial

Abstract: Background: Trichomonias is the most common non-viral STI among women worldwide and is associated with serious reproductive morbidity, poor birth outcomes and amplified HIV transmission. Single-dose metronidazole therapy has been the treatment of choice for over three decades. There is mounting evidence, however, of high rates of repeat positives following single-dose metronidazole, and among HIVinfected women, bacterial vaginosis (BV) was found to alter treatment efficacy. The purpose of this study was to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 37 publications
(44 reference statements)
2
69
0
Order By: Relevance
“…Zhen-Zhou Luo and colleagues 4 suggest that false positives from nucleic acid amplification tests (NAAT), re-infection, and nonadherence to treatment could have influenced the results of our study, 3 and suggest that more data are needed before changing treatment recommendations to multidose metronidazole. We disagree.…”
Section: Treatment Recommendations For Trichomoniasis In Womenmentioning
confidence: 85%
See 2 more Smart Citations
“…Zhen-Zhou Luo and colleagues 4 suggest that false positives from nucleic acid amplification tests (NAAT), re-infection, and nonadherence to treatment could have influenced the results of our study, 3 and suggest that more data are needed before changing treatment recommendations to multidose metronidazole. We disagree.…”
Section: Treatment Recommendations For Trichomoniasis In Womenmentioning
confidence: 85%
“…Multidose metronidazole has been found to be superior to single-dose metronidazole for the treatment of trichomoniasis in a randomised controlled trial done in women with HIV infection, 1 in a metaanalysis of published comparisons, 2 and in our randomised controlled trial done in women without HIV infection, published in The Lancet Infectious Diseases. 3 The abundance of data indicates that multidose metronidazole should be the first line of treatment for trichomoniasis in women.…”
Section: Treatment Recommendations For Trichomoniasis In Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent multi-center randomized control trial found the 7-day course of metronidazole to be superior to single-dose metronidazole for the treatment of trichomonas (11% vs 19% trichomonas positive at 4 weeks post-therapy). 49 Hence, 7 days of therapy may be indicated. Tinidazole is slightly more effective than metronidazole but is considerably more expensive than generic metronidazole.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…This study was a sub-study of a multi-centered randomized trial of two different doses of metronidazole for the treatment of trichomoniasis. Methods have been described elsewhere, 21 but briefly, study participants were recruited from three clinics: Delgado Personal Health Clinic, Crescent Care Health and Wellness Center in New Orleans, LA and the Jefferson County Department of Health (JCDH) -STD Specialty Clinic in Birmingham, AL. These clinics serve mostly African American, low income women, the demographic group most highly affected by T. vaginalis infections.…”
Section: Methodsmentioning
confidence: 99%